2017
DOI: 10.1038/ncomms14995
|View full text |Cite
|
Sign up to set email alerts
|

Histone variant H2A.J accumulates in senescent cells and promotes inflammatory gene expression

Abstract: The senescence of mammalian cells is characterized by a proliferative arrest in response to stress and the expression of an inflammatory phenotype. Here we show that histone H2A.J, a poorly studied H2A variant found only in mammals, accumulates in human fibroblasts in senescence with persistent DNA damage. H2A.J also accumulates in mice with aging in a tissue-specific manner and in human skin. Knock-down of H2A.J inhibits the expression of inflammatory genes that contribute to the senescent-associated secretor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
127
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(142 citation statements)
references
References 53 publications
13
127
1
1
Order By: Relevance
“…By using different pharmacological inhibitors, our results suggest a dichotomic regulation of expression of p16 INK4a , a growth arrest-related characteristics of senescence, and VEGFα production by CSE-induced senescent CCR6 + Th17 cells, as already reported for the SASP of other cell types 32,33 . In support of this is the selective inhibition of CSE-induced production of VEGFα by NAC pretreatment, in comparison with the antimycin A -sensitivity of CSE-stimulated p16 INK4a expression.…”
Section: Discussionsupporting
confidence: 80%
“…By using different pharmacological inhibitors, our results suggest a dichotomic regulation of expression of p16 INK4a , a growth arrest-related characteristics of senescence, and VEGFα production by CSE-induced senescent CCR6 + Th17 cells, as already reported for the SASP of other cell types 32,33 . In support of this is the selective inhibition of CSE-induced production of VEGFα by NAC pretreatment, in comparison with the antimycin A -sensitivity of CSE-stimulated p16 INK4a expression.…”
Section: Discussionsupporting
confidence: 80%
“…2c). By contrast, we observed that chronic irradiation led to enhanced levels of histone H2A.J, a histone variant recently shown to accumulate specifically in senescent cells 33 . To extend our analyses further, we employed a quantitative protein analysis approach -stable isotope labelling of amino acids in cell culture (SILAC) followed by quantitative mass spectrometry analyses -to measure and compare histone levels in irradiated and non-irradiated cells.…”
Section: Scientific Reports |contrasting
confidence: 72%
“…The author proposed that the appearance of markers of senescence does not mean that the cells are truly senescent, but are exhibiting an adaptive stress response (Webster et al, 2015). 6 | CELLULAR SENESCENCE IS ASSOCIATED WITH AGING-ASSOCIATED DISEASES 6.1 | Cellular senescence is associated with chronic inflammation Senescent cells can normally be recognized and cleared by the immune system (Sagiv & Krizhanovsky, 2013 required for the immune system to recognize senescent cells, which contributes to chronic inflammation and aging-associated diseases (Contrepois et al, 2017). Interestingly, p53 signaling seems to decrease with age, whereas NF-κB signaling is increased.…”
Section: Wnt Signalingmentioning
confidence: 99%